2012
DOI: 10.1177/0961203312438630
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications and prognostic significance of thrombocytopenia in Tunisian patients with systemic lupus erythematosus

Abstract: Our results, concerning North-African SLE patients, confirm the findings of previous studies which suggest that thrombocytopenia correlates with more severe disease and has a negative impact on the survival of lupus patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 29 publications
1
36
1
Order By: Relevance
“… 4 , 13 In some studies, patients who were thrombocytopenic more frequently exhibited neurological manifestations, kidney disorders, and hematological abnormalities. 5 , 6 , 8 10 , 15 , 16 Low complement levels and elevated anti-dsDNA antibody have also been observed among patients with thrombocytopenia. 5 , 15 Furthermore, most previous studies showed that disease activity also correlated with thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 13 In some studies, patients who were thrombocytopenic more frequently exhibited neurological manifestations, kidney disorders, and hematological abnormalities. 5 , 6 , 8 10 , 15 , 16 Low complement levels and elevated anti-dsDNA antibody have also been observed among patients with thrombocytopenia. 5 , 15 Furthermore, most previous studies showed that disease activity also correlated with thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“… 7 In previous studies, the mortality of thrombocytopenic patients with SLE was significantly high. 5 , 6 , 13 , 15 The mortality of thrombocytopenic patients was 24%, which was a significantly higher rate compared with those who were not thrombocytopenic (hazard ratio [HR] = 2.855, P < 0.001). 5 A recent study reported a mortality rate in thrombocytopenic patients of 17.1%, which was significantly different to nonthrombocytopenic patients (HR = 1.79, P = 0.045).…”
Section: Discussionmentioning
confidence: 99%
“…ITP is commonly associated with autoimmune diseases, especially with systemic lupus erythematosus (SLE). The prevalence, clinical characteristics and prognostic impact of ITP in SLE have been well-studied (4,5), providing many insights in clinical management of secondary ITP associated with SLE. Presence of ITP in pSS has been reported by some case reports (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…While gestational thrombocytopenia does not seem to affect maternal and fetal outcomes in pregnancy [23], in malaria patients thrombocytopenia has been associated with malaria severity and prognosis [24]. On the other hand, in SLE patients the effects are not clear, with conflicting reports suggesting no effect [22] or correlation with worse prognosis [25]. Recent data suggests that the pathogenesis of PM is mediated in part by an inflammation-coagulation cycle involving platelets as one of the key components in this cycle [26].…”
Section: Discussionmentioning
confidence: 99%